Applied Anthropology Studies: Definition, Professional Ethics, and Its Development Dynamics in Various Fields of Life - Marzuti Isra; Nur Asyiah; Nazwa Lexano Salsabila siregar; Muhammad Zaky Al Syafiq; Muhammad Anugrah Jaya Tanjung; Immanuel Figo Tambun (INFOKUM, 2025)
Applied anthropology is a branch of anthropology that focuses on the application of anthropological theories and methods in solving real problems in society. This study aiming for describe understanding anthropology applied, principles ethics professional, and dynamics its development in various field life like health, education, business, and policy public. With an interdisciplinary approach, applied anthropology is able to provide solutions based on local culture, strengthen community empowerment, and increase the effectiveness of social interventions. Professional ethics are an important pillar in the implementation of applied anthropology practices, especially in maintaining data integrity, respecting cultural values, and preventing exploitation of participants. Technological developments and globalization also influence anthropologists' approaches to applied practice, demanding continuous adaptation. This study emphasizes the importance of the role of anthropologists in producing inclusive and sustainable policies. Recent references show increasing collaboration between anthropologists and practitioners across sectors, which strengthens the position of applied anthropology as a tool for social transformation.